(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Algunas impresiones personales en torno a la evolución de la asignatura del Derecho Eclesiástico del Estado en las últimas décadas Some remarks on the development of the subject of Law and Religion in Spanish legal studies ABSTRACT: These remarks take as their initial pretext the recent publication of an academic work offering a retrospective view of the development of the subject of Law and Religion in Spanish universities which, in the author’s opinion, is deeply biased and therefore gives a distorted image of both the current situation of this discipline in our legal studies and its future expectations. Against this, the author offers here his own personal impressions on the subject.